Pengaruh Penggantian Bahan Pengisi Semen Dengan Kombinasi Abu Bata Dan Abu Sekam Padi Pada Campuran Aspal AC-WC - Rahmi Afifi; Alfian Malik; Gunawan Wibisono (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Asphalt concrete wearing course (AC-WC) is the top layer in flexible pavement. Asphalt concrete is a mixture of asphalt, coarse aggregate, fine aggregate and filler. Many types of filler have been used to improve asphalt concrete performance. In this research, a combined of brick ash and rice husk ash was used as filler. As wasted products, this mixed filler can be used as an alternative replacement of Portland cement due to their similar chemical compounds. The objective of this research is to analyze Marshall characteristics (stability, flow, volumetric properties and Marshall Quotient) of an ACWC mixture containing a combination of Portland cement and a mixed of 40% brick ash and 60% rice husk ash as filler. Ratios of cement and the mixed ash used were 100:0, 50:50, and 0:100. After obtaining the optimum asphalt content for each different filler variation, Marshall test were performed to obtain flow, stability and density values. The result of tests showed that the composition of filler 50:50 gives Marshall characteristics with stability value of 1250,5 kg and air void of 4,846%. The composition of filler 0:100 gives Marshall characteristics with the highest stability value of 1692,9 kg and the smallest air void of 4,533%, which satisfied the specifications of Bina Marga 2010 Revision 3. Keywords: rice husk ash, brick ash, AC-WC, filler